Renovation of the wooden St. John The Baptist Church in Zaborol village near Rivne in the context of neo-vernacular trends - Rychkov, Petro; Smolińska, Olga (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
In Volhynian architectural heritage the prominent place belongs to wooden churches which are outstanding examples of old vernacular building culture. At the same time a modern renovation of such churches tends to replacing of original exterior wooden planking with PVC siding. This problematic phenomenon can be characterized as neo-venacular trend. It actualizes the problem of preserving the authenticity of such architectural monuments. The example of the St. John the Baptist Church in the Zaborol village near Rivne demonstrates the negative consequences of such renovating work. The need to prevent and control this process is accentuated.